2021
DOI: 10.1007/s43678-021-00129-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Canadian emergency physicians’ experiences and perspectives during the COVID-19 pandemic

Abstract: Background The objective of this study was to explore Canadian emergency physicians' experiences, concerns, and perspectives during the first wave of the coronavirus disease pandemic. Methods This cross-sectional survey of physician members of Pediatric Emergency Research Canada and the Canadian Association of Emergency Physicians explored: personal safety/responsibility to care; patient interactions; ethical issues in pandemic care; institutional dynamics and communication practices. Data analysis was descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
1
24
2
Order By: Relevance
“…Regional studies replicated these concerns around PPE supply. About 49% of physicians working in the emergency department reported concerns around lack of PPE, with 31% occasionally providing care without appropriate PPE ( 49 ) (Canada). Similarly, nursing home staff have reported insufficient or a complete lack of appropriate PPE for weeks ( 58 ) (Belgium).…”
Section: Resultsmentioning
confidence: 99%
“…Regional studies replicated these concerns around PPE supply. About 49% of physicians working in the emergency department reported concerns around lack of PPE, with 31% occasionally providing care without appropriate PPE ( 49 ) (Canada). Similarly, nursing home staff have reported insufficient or a complete lack of appropriate PPE for weeks ( 58 ) (Belgium).…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19-related research has focused on ED physicians’ and nurses’ mental health or burnout [ 7 12 ]. ED physicians report a strong moral obligation to care for patients, while dealing with their own fears of contracting COVID-19 [ 13 ]. Understanding ED workers’ concerns and perspectives is fundamental to design supportive, responsive emergency preparedness policies during this ongoing pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are echoed in survey responses, with participants reporting that masks muffle and attenuate speech, and people with hearing loss reporting more difficulties than those without ( 22 , 33 , 42 , 44 ). However, acoustic and behavioral measures do not capture the psychosocial effects that opaque masks have on communication in terms of limiting ability to recognize emotions from facial expressions, decreasing feelings of engagement in a conversation and emotional connection with the speaker and self-confidence ( 7 , 12 , 14 , 40 , 42 , 59 ), eliciting feelings of loneliness, depression, fear, and anxiety ( 12 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 96%
“…Masks have always been a part of medical practice, however, their now ubiquitous use has had broad impacts on communication within the medical context. In addition to detrimental effects on verbal interactions, masks have been reported to affect HCP-HCP and HCP-patient interpersonal relationships, decrease trust and perceived empathy, create fear and anxiety in patient, and reduce HCP's situational awareness-all of which can subsequently affect quality of care ( 24 , 28 , 30 , 31 , 33 , 34 , 36 , 38 ). Indeed, Trecca and colleagues ( 62 ) reported that more patients with hearing loss attributed problems with surgical masks to the inability to lip read than to the speech being muffled, while the study of Kratzke et al ( 36 ) found patients perceived HCPs to be more empathetic and trustworthy than when they are wearing transparent masks rather than opaque masks.…”
Section: Discussionmentioning
confidence: 99%